The deservingness of the rich: public policy, public opinion and elite discourse - Skilling, PD (Australian Political Studies Association, 2013)
This paper explores the question of the deservingness of the rich, focussing on the factors that inform and influence public opinion. A growing body of literature notes that, while the question of the deservingness of the poor has been the subject of a long-standing academic and policy literature, there has been very little attention paid to similar questions in relation to the rich. This relative absence has been challenged recently in the public sphere by protest movements, such as the Occupy movement with its targeting of the privileged 1%, but it continues to obtain in the policy realm, within which wealth has consistently been constructed as a policy non-problem. This relative absence, moreover, is socially important. If societies are to develop policy settings that meaningfully address the socially damaging effects of current high levels of economic inequality then policy makers will need to contemplate policy settings that affect those at the top – as well as those at the bottom – of the economic distribution. Public opinion surveys consistently demonstrate a broad public presumption in favour of the deservingness of the rich to keep what they have earned “through their own efforts” in the market. The paper’s argument is based on a critical discourse analysis of how the issue of the deservingness of the rich has been constructed in the public sphere by political, media and business elites as well as by dissenting voices. Drawing on this analysis, the paper identifies and analyses the key assumptions that inform and support this socially dominant (yet highly contestable) presumption. In this connection, the paper considers the constitutive power of elite discourse, and stresses the significance of the trope of “equality of opportunity” within Third Way political movements during the 1990s.